(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
Industrial use of azo dyes has been linked to severe environmental damage in the textile and apparel sectors. The breakdown products of many azo dyes are poisonous and mutagenic, posing a threat to human health and the environment. Hence, azo dye wastewater bioremediation is gaining interest. The objective of this study was focused on the biodegradation of an azo dye, Reactive Orange 16 (RO16), in an anaerobic continuous tank reactor operated with digested sludge sample. The digested sludge was used as the organic biodegradation agent for azo dye. The aim was to investigate the fate of the anaerobic RR16 breakdown products during the degradation process. Gas Chromatography-Mass Spectrophotometry (GC-MS) was used to identify RO16 biodegradation metabolites and their corresponding molecular weight. As a result, RO 16 showed about 85.91% decolorization capacity, and the degradation metabolites were detected as pentanoic acid and phenol after seven days of incubation. The degradation mechanism was completed as the azo bond of RO16 was successfully cleaved based on the result of GC-MS, and the proposed pathway of the degradation mechanism is described. The digested palm oil sludge with dye degradation enzymes may provide new avenues for biological waste treatment, especially wastewater bioremediation.